“Woman Surau” Maria Kubtiah’s Work in Building Punjung Island Aisyiah Organization 1946-1995: “Perempuan Surau” Kiprah Maria Kubtiah Dalam Membangun Organisasi Aisyiah Pulau Punjung 1946-1995 - Rezi Oktania; Fansuri Mursal, Irhas; Wita, Gusmira (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
This research aims to analyze development of surau which was originally a traditional educational institution, where Bumiputra children learn traditional norms, ethics, manners and the Islamic religion. In Minangkabau tradition, boys who have reached puberty are prohibited from sleeping in the Rumah Gadang. Traditional surau education was reformed into a madrasa at the beginning of the 20th century. Interestingly, on Punjung Island there is a surau driven by